The Preparation and Quality Evaluation of Biscuit Using Composite Flour by Mixing Wheat Flour, Chickpea Flour, and Peanut Flour - Sangam Dahal; Anish Dangal; Mahalaxmi Pradhananga; Diksha Timsina; Prekshya Timsina (International Journal on Food, Agriculture and Natural Resources, 2022)
The main aim of this study was to determine the best formulation of biscuit using roasted gram flour and roasted peanut flour with wheat flour. Bengal gram flour, peanut flour, and wheat flour were blended in the following ratios: sample A; 2.5:2.5:95, sample B; 5:5:90, sample C; 7.5:7.5:85, sample D; 10:10:80. Initial analysis showed that 7.5% roasted gram flour, 7.5% roasted peanut flour and 85% wheat flour can be blended to prepare quality biscuit. The protein content of biscuit ranged from 6.78% in wheat flour biscuit to 13.67% in composite flour biscuit. Fat (16.63%), crude fiber (1.96%), protein (13.67%), and ash content (2.805%) of composite flour biscuit was higher than that of wheat flour biscuit. The shelf life of the composite flour biscuit was studied for 90 days at 15-day interval. The initial and final values of acid value, peroxide value, and moisture were found to be 0.13 mg KOH/gm, 0.265 mg KOH/gm, 0.86 meq peroxide/kg fat, 1.904 meq peroxide/kg fat, and 4%, 5.1%, respectively.